Basic acoustic parameters of organic solvents used in ultrasonic cleaning - NIEMCZEWSKI, Bogdan; SZLAGOWSKA, Teresa (Archives of Acoustics, 1977)
Sound velocities have been measured and the specific acoustic impedance calculated for the following solvents used in the process of ultrasonic cleaning (commercial technical products): trichloroethylene, tetrachloroethylene, 1,1,1-trichloroethane (Baltane), triehlorotrifluoroethane (Freon TF) and dibromotetrafluoroethane, known as freon 114B2.